Susceptibility of Aedes aegypti larvae to temephos and Bacillus thuringiensis var israelensis in integrated control Susceptibilidade de larvas de Aedes aegypti ao tratamento integrado com temephos e Bacillus thuringiensis var israelensis - Carlos Fernando S. de Andrande; Maurício Modolo (Universidade de São Paulo, 1991)
The susceptibility of field collected Aedes aegypti larvae was evaluated in terms of median lethal time (LT50) and final mortality, when treated with temephos, Bacillus thuringiensis var israelensis as well as mixtures of these two agents. Third instar larvae were shown to be more susceptible than early and late fourth instar ones to the entomopathogen. Survival of some individuals when exposed to temephos suggest possible resistance. Temporal synergism in early fourth instar larvae was detected when they were exposed to mixtures of Bti-temephos. The possibility of this integrated treatment is commented on. A susceptibilidade de larvas de Aedes aegypti coletadas no campo foi avaliada em termos do tempo letal mediano (TL50) e da mortalidade final, quando tratadas com temephos, Bacillus thuringiensis var israelensis ou misturas desses dois agentes. As larvas de terceiro estádio mostraram-se mais suceptíveis ao patógeno do que aquelas no início ou no fim do quarto estádio. A sobrevivência de alguns indivíduos aos tratamentos com temephos permite sugerir a possibilidade de resistência. Foi detectada a existência de sinergismo temporal, quando larvas no início do quarto estádio foram tratadas com as misturas do Bti com o temephos. A possibilidade do tratamento integrado é comentada.